Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Ivanova, Maria S. (Zootaxa, 2017)
A new species of the genus Aemene Walker, 1854, Aemene eudonioides Volynkin & Černý, sp. nov. is described from North Thailand and Myanmar. The diagnostic comparison is made with Aemene taeniata Fixsen, 1887. The new synonymy is established: Aemene taeniata (Fixsen, 1887) = Siccia v-nigra Hampson, 1900, syn. nov. The checklist of Aemene taxa from the Oriental and Palaearctic Regions is presented.